Characteristics of genetic alterations of peripheral T‐cell lymphoma in childhood including identification of novel fusion genes: the Japan Children's Cancer Group (JCCG). (13th July 2021) - Ohki, Kentaro; Kiyokawa, Nobutaka; Watanabe, Satoru; Iwafuchi, Hideto; Nakazawa, Astuko; Ishiwata, Keisuke; Ogata‐Kawata, Hiroko; Nakabayashi, Kazuhiko; Okamura, Kohji; Tanaka, Fumiko; Fukano, Reiji; Hata, Kenichiro; et al.
Summary: Peripheral T‐cell lymphoma (PTCL) is a group of heterogeneous non‐Hodgkin lymphomas showing a mature T‐cell or natural killer cell phenotype, but its molecular abnormalities in paediatric patients remain unclear. By employing next‐generation sequencing and multiplex ligation‐dependent probe amplification of tumour samples from 26 patients, we identified somatic alterations in paediatric PTCL including Epstein–Barr virus (EBV)‐negative (EBV – ) and EBV‐positive (EBV + ) patients. As recurrent mutational targets for PTCL, we identified several previously unreported genes, including TNS1, ZFHX3, LRP2, NCOA2 and HOXA1, as well as genes previously reported in adult patients, e.g. TET2, CDKN2A, STAT3 and TP53 . However, for other reported mutations, VAV1 ‐related abnormalities were absent and mutations of NRAS, GATA3 and JAK3 showed a low frequency in our cohort. Concerning the association of EBV infection, two novel fusion genes: STAG2‐AFF2 and ITPR2‐FSTL4, and deletion and alteration of CDKN2A/2B, LMO1 and HOXA1 were identified in EBV – PTCL, but not in EBV + PTCL. Conversely, alterations of PCDHGA4, ADAR, CUL9 and TP53 were identified only in EBV + PTCL. Our observations suggest a clear difference in the molecular mechanism of onset between paediatric and adult PTCL and a difference in the characteristics of genetic alterations between EBV – and EBV + paediatric PTCL.